Trouble at the top? Restricted distribution and extreme population isolation in an alpine crustacean assemblage with unexpected lineage diversity. (November 2016) - Hatley, Jude; Murphy, Nicholas P.
Summary: The fragile alpine freshwater ecosystems of Australia are threatened by historic land use and projected climate change, yet little is known about the fauna of these environments. The aim of this study was to analyse the phylogeography of two important components of this ecosystem, an amphipod ( Neoniphargus ) and an isopod ( Coluboltelson ), to determine the potential impacts of environmental change on these crustaceans. DNA sequences were generated for the mitochondrial cytochrome c oxidase subunit I ( COI ) and nuclear 28S ribosomal RNA ( 28S ) of 229 amphipods and 153 isopods from 19 sites across seven creeks in the Bogong High Plains, Victoria, Australia. Phylogenetic analyses were undertaken to define evolutionary significant units (ESUs), and population genetic structure was examined. Analyses of both markers found deep divergences in both taxa, leading to the definition of six amphipod and two isopod ESUs, within both Neoniphargus and Colubotelson . The majority of amphipod ESUs exhibited highly restricted distributions, with essentially no gene flow between sites, even within the same creeks, consistent with the Death Valley Model of population connectivity. By contrast, both isopod ESUs had overlapping distributions across the entire sample area and exhibited some highly limited population connectivity among sites in adjacent headwaters, consistent with the Headwater Model. This study suggests that there is a high level of undiscovered biodiversity within Australian alpine aquatic invertebrates. The highly limited population structure, and restricted distributions have important consequences for the conservation of the headwaters of Australia's largest river system. These findings indicate that habitat loss and/or fragmentation associated with environmental change will result in biodiversity reductions, with species unlikely to shift their ranges in response to future climate change, or recover rapidly from localised extinction events.